T‐cell replete haploidentical stem cell transplantation with low dose anti‐thymocyte globulin for relapsed/refractory Ewing sarcoma family tumors - Hideki Sano; Kazuhiro Mochizuki; Shogo Kobayashi; Yoshihiro Ohara; Nobuhisa Takahashi; Shingo Kudo; Kazuhiko Ikeda; Hitoshi Ohto; Atsushi Kikuta (Cancer Reports, 2022)
Abstract Background Despite intensive multimodal therapies, the prognosis of relapsed/ refractory Ewing sarcoma family tumors (RR‐ESFTs) is dismal. Some case reports using allogeneic stem cell transplantation (allo SCT) for RR‐ESFTs have been reported, however, the efficacy of allo SCT is yet to be established. Aim The purpose of this study was to evaluate the response and toxicity of T‐cell replete haploidentical SCT (TCR‐haplo‐SCT) in RR‐ESFTs. Methods and results In this study, we retrospectively analyzed six patients with RR‐ESFTs who received TCR‐haplo‐SCT. Four patients had relapsed and two patients had refractory Ewing sarcoma. Before the TCR‐haplo‐SCT, all patients received a reduced intensity‐conditioning regimen containing fludarabine, melphalan, and low‐dose rabbit anti‐thymocyte globulin (2.5 mg/kg), as well as graft‐versus‐host disease (GVHD) prophylaxis, which consisted of tacrolimus, methotrexate, and prednisolone. Primary neutrophil engraftment was achieved in all the patients. Four patients developed acute GVHD (aGVHD) (grade I, 1; grade II, 1; grade III, 2), and two patients developed chronic GVHD (cGVHD). Among the four that developed aGVHD, three survived for 14, 116, and 129 months without relapse, while one died due to a transplant‐related complication. In contrast, the two patients who did not develop aGVHD experienced relapse early after TCR‐haplo‐SCT. Conclusions In this study, three of the six patients with RR‐ESFTs survived for more than one year without relapse, and the treatment toxicity was considered acceptable even for patients who underwent high‐intensity pretreatment. TCR‐haplo‐SCT could be a potential therapeutic option for patients with RR‐ESFTs.